The problems of organization and legal responsibility (civil and administrative) in the field of telecommunications in Iraq - Abdulridha, Jaafar Naser; Gadder, Ghani Ressan (Cuestiones Políticas, 2020)
The objective of the investigation is to analyze problems of organization and legal responsibility (civil and administrative) in the field of telecommunications in Iraq. The methodological basis of research consists of dialectical approaches, as well as special methods of studying legal, comparative-legal, structural-functional phenomena. Mobile phone use has spread widely among consumers. The mobile phone revolution has transformed lifestyles and livelihood resources with their envelopes to creating new business activities and changing the way people communicate. It is concluded that the use of a mobile phone has many effects, which can be social, physical, sanitary, environmental, or legal. For the latter, we note in Iraq that there is no legal regulation of communications that adheres to the provisions of consignment service providers in their relationship with subscribers. In this way, some communications authorities took on the task of creating the legal, political and administrative conditions by issuing policies that identify, in many cases, the conditions to which the mobile service provider includes in the service contract.